2022
DOI: 10.3390/agriculture12050699
|View full text |Cite
|
Sign up to set email alerts
|

Compost and Biostimulants versus Mineral Nitrogen on Productivity and Grain Quality of Two Wheat Cultivars

Abstract: To reduce the environmental pollution, this study was designed to test the effect of using compost and biostimulants as total or partial replacement for mineral nitrogen on productivity and grain quality of two wheat cultivars. Two field experiments were conducted in the Desert Experimental Station, Cairo University located at Wadi El-Natroon, Egypt during two successive seasons (2016/2017 and 2017/2018). A split-split-plot design in a randomized complete block arrangement was used. Four fertilizer treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…The data of Table 12 indicated that there was a significant decrease in the percentage of the average carbohydrate content when the treatment in which the physiological stimulant was not sprayed amounted to 70.35%.The evidence also recorded the highest percentage of average carbohydrate content when spraying with physiological activator in the elongation and booting stage, which amounted to 77.03%. The content of chlorophyll, which led to its contribution to the construction of vegetable growth that work with high efficiency for the metabolism process, which was positively reflected in the stage of filling the grains, where it increased the accumulation of nutrients such as starch in the grain area in addition to the presence of micro-nutrients such as zinc and manganese.This is in agreement with [66], who showed that the increase in the content of carbohydrates and amylose in the potato crop treated with seaweed extract to the presence of micro nutrients such as zinc and manganese in seaweed extract with growth regulators [67], also indicated that the use of biostimulating fertilizers increases the carbohydrate content in grains because it contains substances such as amino acids, potassium phosphate, calcium pantothenate, zinc sulfate and ascorbic acid. As explained by [68], when using seaweed fertilizers with other fertilizers, it increases the starch content in sweet corn and due the reason for this to the nutrients present in the extract such as Cu, Mn and Zn and their important role in the metabolism process.…”
Section: Carbohydrate Content (%)supporting
confidence: 90%
“…The data of Table 12 indicated that there was a significant decrease in the percentage of the average carbohydrate content when the treatment in which the physiological stimulant was not sprayed amounted to 70.35%.The evidence also recorded the highest percentage of average carbohydrate content when spraying with physiological activator in the elongation and booting stage, which amounted to 77.03%. The content of chlorophyll, which led to its contribution to the construction of vegetable growth that work with high efficiency for the metabolism process, which was positively reflected in the stage of filling the grains, where it increased the accumulation of nutrients such as starch in the grain area in addition to the presence of micro-nutrients such as zinc and manganese.This is in agreement with [66], who showed that the increase in the content of carbohydrates and amylose in the potato crop treated with seaweed extract to the presence of micro nutrients such as zinc and manganese in seaweed extract with growth regulators [67], also indicated that the use of biostimulating fertilizers increases the carbohydrate content in grains because it contains substances such as amino acids, potassium phosphate, calcium pantothenate, zinc sulfate and ascorbic acid. As explained by [68], when using seaweed fertilizers with other fertilizers, it increases the starch content in sweet corn and due the reason for this to the nutrients present in the extract such as Cu, Mn and Zn and their important role in the metabolism process.…”
Section: Carbohydrate Content (%)supporting
confidence: 90%
“…Our results agreed with these of Saly-Saleh [52] who studied that wheat flour had low values in protein, fat and fiber compared with composite wheat. And nearly with Abbas et al [53] who reported genotypes wheat carbohydrates ranged from 84.97% to 89.14%, fat content from 0.58% to 2.57% and fiber from 1.18% to 2.91%. On the other hand, our results similar with these of Dossa et al [54] who found that the sesame seeds oil 53.0% and protein content 20.4%.…”
Section: Chemical Composition Of Raw Materialssupporting
confidence: 72%
“…Thereby, a modification in physical and chemical characteristics of soil, organic matter, and different nutrients resulted in increasing growth and yield, this could improve the contents of osmoprotectants in the plant cells [71,72]. Besides, the application of bio-fertilizers like compost, it was found to increase the availability of both macro-and micronutrients to plants, where it plays an important role in metabolic activities including proteins and sugars synthesis [73]. However, the amount of proline and MDA accumulation was significantly reduced, indicating that compost treatments can reduce the severity of Cd-induced osmotic imbalance in barley plants.…”
Section: Discussionmentioning
confidence: 99%